Understanding communication patterns in coping with stress in Indonesia’s gig economy - Juddi, Moh Faidol; Aprianti, Agus; Hameed, Rana Ahmed (Jurnal Kajian Komunikasi, 2025)
Background: Despite the rise of the gig economy, the mental health of Indonesia’s gig workers has received little attention. To cope with work-related stress and a limited interaction between drivers and app firms, many ride-hailing drivers have formed shared experience-based communities, such as Indriver Bandung Bersatu (IBB). Purpose: This study aimed to investigate the perspectives and motives of five drivers in a natural setting, with an emphasis on their lived experiences and interpretations of stress coping mechanisms. Method: To better understand how drivers deal with mental health difficulties at work, a qualitative phenomenological approach was applied. From November to December 2022, data were collected through in-depth interviews and observations. Triangulation and member checking confirmed data validity. Result: Although ride-hailing employment have several advantages, drivers are stressed because of monopolistic policies, fluctuating pay, negative customer behavior, and rapid system modifications. To cope, people rely on personal strength and mutual support from a community that shares experiences and alleviates emotional pressures. Conclusion: Capitalist structures, aided by uneven and unfriendly policies, disadvantaged drivers. Mutual-aid communities, on the other hand, enable them to support one another and work together to find common answers. Implications: Facing shared workplace issues together, sharing experiences, and developing peer-based support all promote motivation and self-determination, allowing drivers to become more resilient.